PENGARUH KECERDASAN EMOSIONAL TERHADAP KEPUASAN DAN KINERJA KARYAWAN PT. JASA RAHARJA (PERSERO) CABANG BALI - Wirawan, Putu Agus Erik Sastra (Jurnal Ekonomi dan Bisnis Jagaditha, 2017)
PT. Jasa Raharja (Persero) is a State Owned Enterprise engaged in social insurance and compulsory insurance which has the main task of collecting funds from the public through Iuran Wajib (IW) and Sumbangan Wajib Dana Kecelakaan Lalulintas Jalan (SWDKLLJ) and channel funds to the victims of traffic accidents both on land, sea, or air. PT. Jasa Raharja (Persero) always trying to improve performance in the field through increased absorption accident compensation payments and an increase in the speed of payment of compensation to the community, in which the performance improvement can not be separated from the role of emotional intelligence employees in maintaining customer relationships for in this case is the community and maintain good relationships into or out of the company so that the creation of a conducive atmosphere and the company's existence is expected to create an employee satisfaction that can affect the performance of employees is increasing. This study aims to investigate the influence of emotional intelligence on employee satisfaction and performance. Respondents in this study were all employees PT. Jasa Raharja (Persero) Branch Bali some 52 people. This study is a census because it uses the entire polulasi as respondents were then processed using the Partial Least Square (PLS). Based on the results of the analysis showed that emotional intelligence and a significant positive effect on satisfaction and employee performance and employee satisfaction and a significant positive effect on employee performance. The study also found that that employee satisfaction is able to mediate emotional intelligence on the performance of employees. Managerial implications that can be applied PT. Jasa Raharja (Persero) is to improve the promotion of policies to be more open, honest, and based on the achievement by implementing a performance appraisal system that already exists objectively as determinants of policy campaign, while the supervisor or supervision is expected to be able to more master work, able to understand and listen to subordinates and give attention so that employee satisfaction in terms of non-material being met.